Urban and peri-urban agriculture and forestry: Transcending poverty alleviation to climate change mitigation and adaptation - Lwasa, Shuaib; Mugagga, Frank; Wahab, Bolanle; Simon, David; Connors, John; Griffith, Corrie (Urban Climate, 2014)
A range of published and grey literature over the last three decades has underlined the importance of urban and peri-urban agriculture and forestry (UPAF) in cities of developing regions. The focus in the published literature is on livelihoods, poverty reduction and ecosystems services at multiple city scales. Cities of developing regions, particularly in Africa, are searching for ways of addressing the unavoidable impacts of climate change and UPAF has demonstrated scalable adaptation and mitigation potential. However, evidence of UPAF’s role in mitigating and adaptation to climate change is scattered in various reports and has not been synthesized for its potential role in developing urban adaptation strategies. Building on the earlier poverty reduction focus of UPAF research, this paper contributes to UPAF knowledge regarding mitigating and adapting to climate change in urban and peri-urban areas in East and West Africa. The paper reports a synthesis based on a systematic review of the available literature on these regions, and selected sources on other parts of sub-Saharan Africa. The paper also examines the extent to which literature conveys any evidence for UPAF playing a role in mediating the effects of climate/environmental change. Limited empirical verification was undertaken in Kampala and Ibadan, but this does not form the basis for systematic generalization. The key emerging areas of adaptation and mitigation include enhanced food security, productive greening, ecosystem services and innovative policy for urban resilience and transformation.
Keywords: Urban agriculture; Urban forestry; Climate Change; Adaptation; Mitigation; Urban Africa